Role of Workplace Spirituality and Organizational Citizenship Behavior (OCB) In Improving Lecturers’ Performance - Ramilan Ramilan; Rita Yuni Mulyanti; Koesmawan Koesmawan; Lela Nurlaela Wati (Research Synergy Foundation, 2024)
Educators serve as primary stakeholders profoundly shaping the caliber of tertiary educational establishments. Various determinants impact educator performance, encompassing competencies, motivational factors, discipline, and leadership qualities, as well as Organizational Citizenship Behavior (OCB), where employees’ actions surpass their primary job responsibilities. This study intends to experimentally demonstrate the impact of workplace spirituality on the productivity of Lecturers in the Muhammadiyah Aisiyah College (PTMA) setting, both directly and indirectly. To gather empirical data on the impact of workplace spirituality on the performance of PTMA lectures, this study used a quantitative method with a causality design. A questionnaire completed by 260 academics was used to obtain the data. The PLS method and structural equation modeling were used to examine the data. processing data with the SMARTPLS program. According to the study's findings, OCB is positively and significantly influenced by the spiritual workplace, and both OCB and performance are positively and significantly impacted by the spiritual workplace's impact on PTMA lecturers’ performance. The final significant finding is that OCB can enhance performance in spiritual workplaces. These findings have consequences for PTMA managers, and it is vital to encourage an increase in OCB by bolstering the spiritual workplace in the PTMA they oversee to boost the performance of their lecturers.